The Psychological Significance of Quality of Life for Mexican Adolescents - Guadarrama Guadarrama, Rosalinda; Hernández Navor, Julio César; Veytia López, Marcela; Márquez Mendoza, Octavio (Pensando Psicología, 2014)
The first objective of this research was to determine the psychological significance of the concept of quality of life among a sample of 300 Mexican adolescents aged from 12 to 16, using a technique of semantic networks. This technique enables close study of the collective significance of an object, word or expressions, with the emphasis on cognitive processes, in order to understand their interpretation and the repercussions of this on a subject’s mental health. The second objective of the study was to determine the dimensions of the concept of quality of life in Mexican adolescents. The results, both generally and by gender, indicate that Mexican adolescents interpret the concept of quality of life as a general state of satisfaction primarily consisting of elements such as belonging to a family, love and health, which are spread across each of the ten dimensions found in the research. In conclusion it was found that quality of life in Mexican adolescents is defined based on the interaction of multiple psychosocial and personal factors with which the subject can realize their potential to achieve wellbeing and satisfaction in the context they live in.